Skeletal Muscle Quality: A Biomarker for Assessing Physical Performance Capabilities in Young Populations - Naimo, Marshall A.; Varanoske, Alyssa N.; Hughes, Julie M.; Pasiakos, Stefan M. (Frontiers in Physiology, 2021)
Muscle quality (MQ), defined as the amount of strength and/or power per unit of muscle mass, is a novel index of functional capacity that is increasingly relied upon as a critical biomarker of muscle health in low functioning aging and pathophysiological adult populations. Understanding the phenotypical attributes of MQ and how to use it as an assessment tool to explore the efficacy of resistance exercise training interventions that prioritize functional enhancement over increases in muscle size may have implications for populations beyond compromised adults, including healthy young adults who routinely perform physically demanding tasks for competitive or occupational purposes. However, MQ has received far less attention in healthy young populations than it has in compromised adults. Researchers and practitioners continue to rely upon static measures of lean mass or isolated measures of strength and power, rather than using MQ, to assess integrated functional responses to resistance exercise training and physical stress. Therefore, this review will critically examine MQ and the evidence base to establish this metric as a practical and important biomarker for functional capacity and performance in healthy, young populations. Interventions that enhance MQ, such as high-intensity stretch shortening contraction resistance exercise training, will be highlighted. Finally, we will explore the potential to leverage MQ as a practical assessment tool to evaluate function and enhance performance in young populations in non-traditional research settings.